Subtle transcriptomic response of Eurasian perch (Perca fluviatilis) associated with Triaenophorus nodulosus plerocercoid infection - Taube Konrad; Noreikiene Kristina; Kahar Siim; Gross Riho; Ozerov Mikhail; Vasemägi Anti (Elsevier Ltd, 2025)
Determining the physiological effects of parasites and characterizing genes involved in host responses to infections are essential to improving our understanding of host-parasite interactions and their ecological and evolutionary consequences. This task, however, is complicated by high diversity and complex life histories of many parasite species. The use of transcriptomics in the context of wild-caught specimens can help ameliorate this by providing both qualitative and quantitative information on gene expression patterns in response to parasites in specific host organs and tissues. Here, we evaluated the physiological impact of the widespread parasite, the pike tapeworm (Triaenophorus nodulosus), on its second intermediate host, the Eurasian perch (Perca fluviatilis). We used an RNAseq approach to analyse gene expression in the liver, the target organ of T. nodulosus plerocercoids, and spleen which is one of the main immune organs in teleost fishes. We compared perch collected from multiple lakes consisting of individuals with (n = 8) and without (n = 6) T. nodulosus plerocercoids in the liver. Results revealed a small number of differentially expressed genes (DEGs, adjusted p-value ≤0.05) in both spleen (n = 22) and liver (n = 10). DEGs in spleen consisted of mostly upregulated immune related genes (e.g., JUN, SIK1, THSB1), while those in the liver were often linked to metabolic functions (e.g., FABP1, CADM4, CDAB). However, Gene Ontology (GO) analysis showed lack of functional enrichment among DEGs. This study demonstrates that Eurasian perch displays a subtle response at a gene expression level to T. nodulosus plerocercoid infection. Given that plerocercoids are low-metabolic activity transmission stages, our results suggest that moderate T. nodulosus plerocercoid infection most likely does not provoke an extensive host immune response and have relatively low physiological costs for the host. Our findings illustrate that not all conspicuous infections have severe effects on host gene regulation.